Small for gestational age newborn infants. The effect of standard curves of birth weight on the calculation of the prevalence and of the risk factors. - Rodrigues, T (1996)
Sampling decisions, statistical methods and criteria for dating pregnancy all influence birth-weight percentiles and the ability to classify a newborn as growth retarded or small for date. Consequently the prevalence of small for date, the type and the magnitude of risk factors associated with this condition, and the evaluation of preventive interventions are dependent on the standards used. In this study we established birthweight standards for sex and gestational age (36 to 41 weeks) in a sample of 7518 singleton newborns delivered from 1989-92 at Famalicão Hospital. Later, these reference percentiles were applied to a sample of 2210 to calculate the prevalence of small for date, to evaluate associated risk factors, and to compare these estimates with those obtained using Thompson or Lubchenco published charts. The prevalence of small for gestational age was significantly higher using local standards (9.9 or 10.0%) when compared with those obtained using Thompson (8.8%, p < 0.005) or Lubchenco (4.4%, p < 0.005) percentiles. However, the risk factors identified and the magnitude of the point estimates for odds ratios were similar regardless of the reference percentiles. This study shows a significant misclassification of newborns as small or adequate for gestational age that may affect individual prognosis, but this is not reflected in the type and the importance of detected risk factors at a group level.